Little Melba and her big trombone - Russell-Brown, Katheryn, 1961- (Lee & Low Books, 2014)
"A biography of African American musician Melba Doretta Liston, a virtuoso musician who played the trombone and composed and arranged music for many of the great jazz musicians of the twentieth century. Includes afterword, discography, and sources"--